2019
DOI: 10.1007/s42380-019-00027-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Students’ Grade Level, Gender, and Form of Bullying Victimization on Coping Strategy Effectiveness

Abstract: Bullying victimization is a pervasive problem nationwide and is related to students' psychological distress, including increased loneliness, anxiety, depression, helplessness, and suicidal behaviors. Importantly, not all students respond to peer victimization in the same way. This study examined the effectiveness of students' coping strategies in response to bullying as a function of their grade level, gender, and form of victimization. Students in grades five through twelve (N = 2627) completed surveys assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 75 publications
2
12
0
4
Order By: Relevance
“…Nevertheless, research findings on the benefits of social support seeking have also been mixed. For example, Machmutow et al (2012) found that those who reported seeking out the support of a close friend after being victimized experienced lower levels of depression, consistent with other studies finding seeking friend support to be helpful for both boys and girls in reducing risk for maladjustment in the face of peer victimization (e.g., Nixon et al, 2019). Similarly, adolescents who reported having a friend whom they felt comfortable going to for advice had lower levels of depressive symptoms following peer victimization (Hodges et al, 1999).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, research findings on the benefits of social support seeking have also been mixed. For example, Machmutow et al (2012) found that those who reported seeking out the support of a close friend after being victimized experienced lower levels of depression, consistent with other studies finding seeking friend support to be helpful for both boys and girls in reducing risk for maladjustment in the face of peer victimization (e.g., Nixon et al, 2019). Similarly, adolescents who reported having a friend whom they felt comfortable going to for advice had lower levels of depressive symptoms following peer victimization (Hodges et al, 1999).…”
supporting
confidence: 79%
“…Furthermore, research has found that boys are much less likely than girls to seek social support, especially about peer stress (Eschenbeck et al, 2007), and are less likely to view it as an effective strategy for coping with peer victimization (Hunter et al, 2004). Despite this, help-seeking behavior for a variety of stressors including peer victimization has been found to protect both boys and girls from psychological maladjustment (Heerde & Hemphill, 2018), especially among younger adolescents (Nixon et al, 2019).…”
mentioning
confidence: 99%
“…Bullying reports by students to teachers and other adult authorities are often necessary to get their attention and interventions, and such help seeking has been found to be the most effective bullying coping strategy (Nixon et al, 2019). Cortes and Kochenderfer-Ladd (2014) examined a sample of elementary school students and found those who were more willing to report bullying had lower levels of bullying victimization.…”
Section: Background On Bullying Reporting Concerns and School Climatementioning
confidence: 99%
“…Positive refocusing merupakan upaya untuk mengarahkan pikiran kepada hal-hal yang menyenangkan, sementara positive reappraisal yaitu pemaknaan positif terhadap suatu peristiwa sebagai bagian dari pertumbuhan personal (Garnefski, Kraaij, dan Spinhoven, 2001). Temuan penelitian membuktikan strategi coping yang melibatkan cognitive refocusing berhubungan dengan rendahnya pengalaman emosional negatif (Nixon et al, 2019), sehingga memungkinkan individu bergerak menuju perubahan yang lebih positif.…”
Section: Pengertian Posttraumatic Growthunclassified